2018
DOI: 10.3390/app8071037
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Abrasive Flow Processing Method for Complex Geometric Surfaces of Titanium Alloy Artificial Joints

Abstract: Featured Application: A new material removal theoretical model of abrasive flow is set up, and it can offer solution scheme of fluid-based precise processing for workpieces with irregular geometric structures. An improved abrasive flow processing method is proposed to provide direct technical supports for the manufacturing of titanium alloy artificial joints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Sun et al 42 conducted a simulation study of the SAF in the constrained flow channel using the wall function method and the turbulent model and obtained the distribution of the parameters in the flow channel, for instance the turbulent kinetic energy, the velocity, the dynamic pressure, and the wall shear stress of abrasive flow; thus, a method to change the structure of the constrained module was proposed to optimize and regulate the turbulent flow of the abrasive particle in the constrained flow channel. Zhang et al 43 proposed an improved abrasive flow processing method and provided a new material removal model of abrasive flow to reveal the processing regularities for complex geometric surfaces of titanium alloy artificial joints. The numerical and processing experiment results indicated that the proposed material removal model can estimate the processing effects and removal regularities, and the size accuracy and surface quality of the titanium alloy surface are improved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al 42 conducted a simulation study of the SAF in the constrained flow channel using the wall function method and the turbulent model and obtained the distribution of the parameters in the flow channel, for instance the turbulent kinetic energy, the velocity, the dynamic pressure, and the wall shear stress of abrasive flow; thus, a method to change the structure of the constrained module was proposed to optimize and regulate the turbulent flow of the abrasive particle in the constrained flow channel. Zhang et al 43 proposed an improved abrasive flow processing method and provided a new material removal model of abrasive flow to reveal the processing regularities for complex geometric surfaces of titanium alloy artificial joints. The numerical and processing experiment results indicated that the proposed material removal model can estimate the processing effects and removal regularities, and the size accuracy and surface quality of the titanium alloy surface are improved.…”
Section: Introductionmentioning
confidence: 99%
“…The turbulence intensity of SAF in the constrained flow passage is the key factor to determine the processing effects. Relevant scholars [34][35][36][37][38][39][40][41][42][43] have carried out a series of research works about the designs of the sliding constrained module, dual-inlet constrained flow channel, hedging perturbation flow channel, and the structure of changing confined flow channel, in which the processing efficiency and polishing uniformity have been improved. Obviously, the SAF finishing is a new effective method for precision processing on the complex structured surfaces of the mold.…”
Section: Introductionmentioning
confidence: 99%
“…Both solutions inherently involve the band-pass filter (BPF), rectifier or absolution algorithm and low-pass filter (LPF) to isolate the fundamental ripples of the coil current and voltage. Lu et al [ 17 ], Zhang et al [ 18 , 19 ], Pan et al [ 20 ] and Tan et al [ 21 , 22 ] investigated the digital model of amplitude demodulation. Similarly, Yu et al [ 23 ] and Li et al [ 24 , 25 ] improved the estimation accuracy using an accurate analytical model in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%
“…However, the geometric shape of artificial joints is complex [9], so it is difficult to plan the laser cladding path. How to design a suitable laser cladding path on such a complex surface and improve the efficiency and quality of coatings preparation has become an urgent problem to be solved.…”
Section: Introductionmentioning
confidence: 99%